2015
DOI: 10.1248/bpb.b14-00505
|View full text |Cite
|
Sign up to set email alerts
|

The Glucagon-Like Peptide-1 Analogue Liraglutide Inhibits Oxidative Stress and Inflammatory Response in the Liver of Rats with Diet-Induced Non-alcoholic Fatty Liver Disease

Abstract: Liraglutide, a glucagon-like peptide-1 (GLP-1) analogue, has been demonstrated to reduce hepatic steatosis. However, the mechanism of the lipid-lowering effect of liraglutide in the liver remains unclear. The aim of the present study was to investigate the beneficial effect of liraglutide on diet-induced non-alcoholic fatty liver disease (NAFLD) and the underlying mechanism in rats. NAFLD was induced in Sprague-Dawley rats by feeding a high fat and high cholesterol (HFHC) diet. Liraglutide (0.6 mg/kg body weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 58 publications
8
36
0
Order By: Relevance
“…It has been reported that activators of GLP-1 receptors can regulate lipid metabolism and homocysteine enzymes (Wang et al, 2014;Gao et al, 2015;Liu et al, 2014;Niu et al, 2015), so we observed the effect of our liraglutide-loaded PLGA microspheres on these. The microspheres have positive effects in improving lipid metabolism and homocysteine enzyme levels.…”
Section: Tablesupporting
confidence: 57%
See 2 more Smart Citations
“…It has been reported that activators of GLP-1 receptors can regulate lipid metabolism and homocysteine enzymes (Wang et al, 2014;Gao et al, 2015;Liu et al, 2014;Niu et al, 2015), so we observed the effect of our liraglutide-loaded PLGA microspheres on these. The microspheres have positive effects in improving lipid metabolism and homocysteine enzyme levels.…”
Section: Tablesupporting
confidence: 57%
“…It has been reported that activators of GLP-1 receptors can regulate lipid metabolism and homocysteine enzymes (Wang et al, 2014;Gao et al, 2015;Liu et al, 2014;Niu et al, 2015). From Fig 7, we can see that except for cystathionine beta-synthase, where similar quantities are observed for all groups, the three microsphere groups and the LCIG treatment group have distinct effects on the metabolic enzyme profile.…”
Section: Metabolic Enzymesmentioning
confidence: 53%
See 1 more Smart Citation
“…Additionally, atorvastatin increase intrarenal activities of SOD and decrease MDA content . Gao et al (2015) show that liraglutide significantly increased SOD levels in non-alcoholic fatty liver disease. Also, it prevented brain edema, suppressed neuroinflammation following intracerebral hemorrhage (Hou et al, 2012).…”
Section: Discussionmentioning
confidence: 82%
“…These effects were observed in experimental animals but also in the clinical setting. Liraglutide, for example improves metabolic dysfunction and insulin resistance, reduces lipotoxicity in the liver, and counteracts the pathogenesis of nonalcoholic hepatic steatosis [48,49 & ].…”
Section: Effect Of Glucagon-like Peptide-1 To Improve Hepatic Steatosismentioning
confidence: 99%